Biodegradation Of Diethyl Phthalate (DEP) Using Fungi Isolated From Leachate Of Sarimukti Landfill, Bandung - Mulyana, Suci; Sembiring, Emenda (Riwayat: Educational Journal of History and Humanities, 2024)
Phthalate compounds that are commonly found in everyday life are diethyl phthalate (DEP). This compound is dangerous because it is carcinogenic,xenoestrogenicand has endocrine disrupting effects. The accumulation of plastic in landfill causes this compound to be identified in leachate with an existing concentration of 1,277 mg/L. Biological treatment is one of the appropriate technologies in DEP removal. The treatment involves the degradation of DEP using fungi isolated fromleacheatesamples. Degradation tests were carried out at varying concentrations of 2 mg/l, 4 mg/l, 6 mg/l, 8 mg/l and 10 mg/l in a test time span of 15 days and analyzed every 3 days. Concentration testing wasperfomedusing High Performance Liquid Chromatography (HPLC). DEP removal efficiency reached 98-99% in each concentration variation on day 9 with a specific fungal growth rate of 0.0002-0.068/day.